Chemical Composition, Antioxidant Potential, and Nutritional Evaluation of Cultivated Sorghum Grains: A Combined Experimental, Theoretical, and Multivariate Analysis - Simona Jaćimović; Biljana Kiprovski; Petar Ristivojević; Dušan Dimić; Đura Nakarada; Biljana Dojčinović; Vladimir Sikora; Nemanja Teslić; Nebojša Đ. Pantelić (MDPI AG, 2023)
Sorghum grain (Sorghum bicolor L. Moench) is a gluten-free cereal with excellent nutritional value and is a good source of antioxidants, including polyphenols, as well as minerals with proven health benefits. Herein, the phenolic composition, elemental profile, and antioxidant activity of sixteen food-grade sorghum grains (S1-S16) grown under agroecological conditions in Serbia were determined. Nine phenolic compounds characteristic of sorghum grains, such as luteolinidin, 5-methoxyluteolinidin, luteolidin derivative, luteolidin glucoside, apigeninidin, 7-methoxyapigeninidin, apigeninidin glucoside, and cyanidin derivative, were quantified. The antioxidant potential of the analyzed sorghum grains was evaluated by UV/Vis (DPPH, ABTS, and FRAP) and Electron Paramagnetic Resonance spectroscopy (hydroxyl and ascorbyl radical scavenging assays). The content of macro- and microelements was determined by Inductively Coupled Plasma Optical Emission spectroscopy. Theoretical daily intakes of selected major and trace elements were assessed and compared with the Recommended Daily Allowance or Adequate Intake. Sample S8 had the highest amount of phenolic compounds, while S4, S6, and S8 exhibited the strongest antioxidative potential. The sorghum studied could completely satisfy the daily needs of macro- (K, Mg, and P) and microelements (Se, Zn, Fe). Pattern recognition techniques confirmed the discrimination of samples based on phenolic profile and elemental analysis and recognized the main markers responsible for differences between the investigated samples. The reaction between hydroxyl radicals and luteolinidin/apigeninidin was investigated by Density Functional Theory and thermodynamically preferred mechanism was determined.